2020
DOI: 10.1186/s40623-020-01203-4
|View full text |Cite
|
Sign up to set email alerts
|

Toward comparable relative locations between the mainshock slip and aftershocks via empirical approaches

Abstract: The relative locations between mainshocks and their aftershocks have long been studied to characterize the mainshock-aftershock relationships, yet these comparisons may be subjected to biases inherited from various sources, such as the analysis method, data, and model parameters. Here, we perform both a relocation analysis of interplate events to obtain accurate relative centroid locations and a slip inversion analysis of the mainshock slip relative to the relocated events, with some of the relocated events us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…However, other events have propagated in different directions from their slip direction, such as the large events in the Naka region that initiated around the central hotspot, which grew approximately perpendicular to the slip direction (Figure 5b), and the diverse rupture propagation directions of the large events in the Tsukuba region (Figure 8b). To obtain such directivity information, other approaches such as relative source time function measurements via empirical Green's functions (Abercrombie et al., 2017, 2020; Ammon et al., 1993; Folesky et al., 2018) or amplitude measurements (Boatwright, 2007; Kane et al., 2013) could also be applied. More detailed information regarding rupture processes can also be obtained via slip inversion analysis of the larger events, which would provide more details of the slip growth history, as was done by Okuda and Ide (2018b) on some of the events in the Naka and Kushiro regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other events have propagated in different directions from their slip direction, such as the large events in the Naka region that initiated around the central hotspot, which grew approximately perpendicular to the slip direction (Figure 5b), and the diverse rupture propagation directions of the large events in the Tsukuba region (Figure 8b). To obtain such directivity information, other approaches such as relative source time function measurements via empirical Green's functions (Abercrombie et al., 2017, 2020; Ammon et al., 1993; Folesky et al., 2018) or amplitude measurements (Boatwright, 2007; Kane et al., 2013) could also be applied. More detailed information regarding rupture processes can also be obtained via slip inversion analysis of the larger events, which would provide more details of the slip growth history, as was done by Okuda and Ide (2018b) on some of the events in the Naka and Kushiro regions.…”
Section: Resultsmentioning
confidence: 99%
“…This enables us to compare the relative hypocenter and centroid locations under the same unified coordinate, which yields information on rupture development without the requirement of a more detailed, event‐specific analysis, such as a slip inversion analysis. This approach provides a different perspective on rupture directivity, thereby yielding directivity information simply through high‐resolution hypocenter and centroid locations, without requiring approaches such as relative source time function measurements through empirical Green's functions (Abercrombie et al., 2017, 2020; Ammon et al., 1993; Folesky et al., 2018), or by amplitude measurements (Boatwright, 2007; Kane et al., 2013). We apply this new approach to three study regions in the Tohoku‐Hokkaido subduction zone, Japan (Figure 1), all of which contain repeating earthquakes grouped by Igarashi (2020), and two of which contain large repeating earthquakes that have been studied by Okuda and Ide (2018b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many observations show lower aftershock productivity in large slip areas in the mainshock (Beroza & Zoback, 1993; Chang & Ide, 2020; Das & Henry, 2003; Wetzler et al., 2018). For example, Wetzler et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many observations show lower aftershock productivity in large slip areas in the mainshock (Beroza & Zoback, 1993;Chang & Ide, 2020;Das & Henry, 2003;Wetzler et al, 2018). For example, Wetzler et al (2018) compiled the spatial distribution of aftershocks for a large number of subduction zone earthquakes and statistically found that aftershocks are clustered around the edges of the coseismic slip.…”
Section: Aftershock Clustering Around the Tips Of The Ruptured Faultmentioning
confidence: 99%